ANALYSIS OF NATIONAL MODELS FOR THE FORMATION OF ECONOMIC CLUSTERS IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The review of the competitiveness of this national economy came under the influence of National Economic Policy on the processes taking place in the economy. If the conditions under which the world economy is currently developing-the processes of globalization, the growth of the number of transnational companies and the expansion of the spheres of their activities are taken into account, the issues of developing the competitiveness of the economy, taking into account the location factor, come to the fore